Undertriage of major trauma patients at a university hospital: a retrospective cohort study - Terje Nordgarden; Peter Odland; Anne Berit Guttormsen; Kristina Stølen Ugelvik (Scandinavian Journal of Trauma, Resuscitation and Emergency Medicine, 2018)
Abstract Background Studies show increased mortality among severely injured patients not met by trauma team. Proper triage is important to ensure that all severely injured patients receive vital trauma care. In 2017 a new national trauma plan was implemented in Norway, which recommended the use of a modified version of “Guidelines for Field Triage of Injured Patients” to identify severely injured patients. Methods A retrospective study of 30,444 patients admitted to Haukeland University Hospital in 2013, with ICD-10 injury codes upon discharge. The exclusion criteria were department affiliation considered irrelevant when identifying trauma, patients with injuries that resulted in Injury Severity Score < 15, patients that did receive trauma team, and patients admitted > 24 h after time of injury. Information from patient records of every severely injured patient admitted in 2013 was obtained in order to investigate the sensitivity of the new guidelines. Results Trauma team activation was performed in 369 admissions and 85 patients were identified as major trauma. Ten severely injured patients did not receive trauma team resuscitation, resulting in an undertriage of 10.5%. Nine out of ten patients were men, median age 54 years. Five patients were 60 years or older. All of the undertriaged patients experienced fall from low height (< 4 m). Traumatic brain injury was seen in six patients. Six patients had a Glasgow Coma Scale score ≤ 13. The new trauma activation guidelines had a sensitivity of 95.0% in our 2013 trauma population. The degree of undertriage could have been reduced to 4.0% had the guidelines been implemented and correctly applied. Conclusions The rate of undertriage at Haukeland University Hospital in 2013 was above the recommendations of less than 5%. Use of the new trauma guidelines showed increased triage precision in the present trauma population.